Mechanical testing and comparison of porcine tissue, silicones and 3D-printed materials for cardiovascular phantoms - Illi, Joël; Ilic, Marc; Stark, Anselm Walter; Amstutz, Cornelia; Burger, Juergen; Zysset, Philippe; Haeberlin, Andreas; Gräni, Christoph (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Cardiovascular phantoms for patient education, pre-operative planning, surgical training, haemodynamic simulation, and device testing may help improve patient care. However, currently used materials may have different mechanical properties compared to biological tissue. Methods/Aim: The aim of this study was to investigate the mechanical properties of 3D-printing and silicone materials in comparison to biological cardiovascular tissues. Uniaxial cyclic tension testing was performed using dumbbell samples from porcine tissue (aorta, pulmonary artery, right and left ventricle). Flexible testing materials included 15 silicone (mixtures) and three 3D-printing materials. The modulus of elasticity was calculated for different deformation ranges. Results: The modulus of elasticity (0-60%) for the aorta ranged from 0.16 to 0.18 N/mm2, for the pulmonary artery from 0.07 to 0.09 N/mm2, and for the right ventricle as well as the left ventricle short-axis from 0.1 to 0.16 N/mm2. For silicones the range of modulus of elasticity was 0.02 to 1.16 N/mm2, and for the 3D-printed materials from 0.85 to 1.02 N/mm2. The stress-strain curves of all tissues showed a non-linear behaviour in the cyclic tensile testing, with a distinct toe region, followed by exponential strain hardening behaviour towards the peak elongation. The vessel samples showed a more linear behaviour comparted to myocardial samples. The silicones and 3D printing materials exhibited near-linearity at higher strain ranges, with a decrease in stiffness following the initial deformation. All samples showed a deviation between the loading and unloading curves (hysteresis), and a reduction in peak force over the first few cycles (adaptation effect) at constant deformation. Conclusion: The modulus of elasticity of silicone mixtures is more in agreement to porcine cardiovascular tissues than 3D-printed materials. All synthetic materials showed an almost linear behaviour in the mechanical testing compared to the non-linear behaviour of the biological tissues, probably due to fibre recruitment mechanism in the latter.